Inhibitory Effects of AVEMAR on Proliferation and Metastasis of Oral Cancer Cells. (2nd April 2016) - Yang, Mei-Due; Chang, Wen-Shin; Tsai, Chia-Wen; Wang, Ming-Fu; Chan, Yin-Ching; Chan, Kung-Chi; Lu, Meng-Chun; Kao, Ai-Wen; Hsu, Chin-Mu; Bau, Da-Tian
ABSTRACT: Oral cancer is keeping its 4th rank on the death causing cancers among Taiwan males, and its metastatic and recurrent rates remain high and a life-threatening issue to the citizens. Fermented wheat germ extract (AVEMAR) is used in clinical cancer nutritional therapy in gastrointestinal cancers but not in oral cancer yet. In this study, the potential of AVEMAR to inhibit tumor proliferation and metastasis of oral cancer was first investigated. Antiproliferative activity of AVEMAR was determined in human oral squamous carcinoma SCC-4 cells by MTT methodology. Wound-healing migration, transwell invasion, and Western blotting assays were carried out to examine the in vitro antimetastatic effects and involved signaling molecules for AVEMAR in oral cancer cells. AVEMAR at 0.2–1.6 mg/ml significantly inhibited the cell viability with IC50 values of 1.19 and 0.98 mg/ml for 24-h and 48-h treatment. Furthermore, AVEMAR could induce cell apoptosis and inhibit the migration and invasion of metastatic SCC-4 cells at a similar dose range. Notably, AVEMAR suppressed the expression of matrix metalloproteinase (MMP)-2 and urokinase plasminogen activator (u-PA), but not MMP-1 or MMP-9, in SCC-4 cells. These results strongly support the antiproliferation and in vitro antimetastatic capacity of AVEMAR which may extend its contributions from cancer nutrition supplements to preventive agent for oral cancer.